Pigment mediated biogenic synthesis of silver nanoparticles using diatom Amphora sp. and its antimicrobial activity - Jayashree Jena; Nilotpala Pradhan; Bishnu Prasad Dash; Prasanna Kumar Panda; Barada Kanta Mishra (Journal of Saudi Chemical Society)
Light induced biosynthesis of polycrystalline silver nanoparticles (SNPs) using the aqueous extract of a diatom Amphora-46 was studied. Rapid formation of stable SNPs was observed only on exposure of the reaction mixture to light. Strong surface plasmon resonance at 415 nm due to SNP formation was confirmed by spectroscopic analysis. TEM analysis confirmed the formation of polycrystalline spherical SNPs of an average size of 20–25 nm which was further corroborated by XRD, EDAX and SAED results. Compositional analysis using EDAX showed strong characteristic signal for silver. The XRD spectra show four intense diffraction peaks at 38.48°, 44°, 64.74°, and 77.4° which correspond well to (111), (200), (220), and (311) plane of (fcc) polycrystalline SNP and the intensity of peak at (111) plane is more than the other peaks, suggesting that this plane is the predominant one. Both XRD and SAED results clearly indicated that the SNPs were polycrystalline in nature and were of high purity. The bio-molecule responsible for the reduction of silver ion was identified to be a photosynthetic pigment fucoxanthin, which is light sensitive and acts as a reducing agent. Furthermore, the synthesized SNPs possess significant antimicrobial activity against gram positive and gram negative bacteria. This study demonstrates for the first time, the involvement of photosynthetic pigment fucoxanthin isolated from Amphora-46 in silver nanoparticle formation through a light dependent reaction.